Strengthening Civic Education in Elementary Schools Through a Multiple Intelligence Approach - Muhammad Allif Adzkal Fata Assidqi; Fathurrohman Fathurrohman (Yayasan Zia Salsabila, 2026)
Citizenship Education (PKn) at the elementary school level (SD/MI) plays a strategic role in shaping the character of young citizens grounded in Pancasila values. The challenges of globalization and digitalization demand more adaptive and holistic learning approaches. This article examines the application of Howard Gardner's Multiple Intelligence theory in PKn learning at the SD/MI level as an effort to strengthen the internalization of Pancasila values among students. Through a literature study method, this review explores various previous research to identify the correlation between diverse intelligences and the pedagogical strategies of PKn teachers. The findings indicate that a multiple intelligence approach can accommodate the diversity of student potential, enhance the effectiveness of national values cultivation, and encourage active student engagement in PKn learning. The practical implication of this study is the need for SD/MI teachers to design PKn learning that is responsive to students' multiple intelligences to realize a complete Pancasila Student Profile.